Bioprinting of Skin Tissues: From Concept to Clinical Applications (Journal of Medical Device Technology, 2023)
3D bioprinting, with its vast potential in therapeutic uses, has evolved into a forefront technique for creating skin tissues. This article delves into a thorough analysis of various aspects of bioprinting skin tissues, including strategies, bioinks, clinical applications, challenges, and future outlooks. Different bioprinting strategies, such as laser-assisted, inkjet-based, and extrusion-based techniques, are explored, each offering unique advantages in crafting complex, lifelike skin structures. The composition and cell-friendly nature of collagen-based bioinks are discussed, underlining their significance in establishing a conducive microenvironment for cell survival and tissue development. Clinical applications, particularly in providing personalized treatments for wound healing using bioprinted skin tissue, are examined. The article also investigates the potential uses of tailored and in vitro bioprinted skin models. Challenges, including achieving optimal printability, vascularization, and innervation of various skin components during the bioprinting process, are addressed. Lastly, the article looks forward to future developments, such as transforming regenerative medicine and merging skin bioprinting with other bioprinting technologies.
Keywords: Additive manufacturing; Tissue engineering; 3D bioprinting; Skin bioprinting; Bioinks